Energy and Exergy Analyses of Egyptian Cement Kiln Plant with Complete Kiln Gas Diversion through by Pass - Laila M. Farag (International Journal of Advances in Applied Sciences, 2012)
The present article deals with evaluation of energy and exergy efficiences of an Egyptian  dry process cement kiln plant  with precalciner  characterized by that  the whole kiln gas is diverted through  by pass . Such diversion is necessary to break the intense cycles of   secondary constituents  Cl, alkalis and sulfur that may arise  between precaciner -preheater and kiln due to the high content of the raw materials of such secondary constituents. Based on average actual operation data  of the process, energy and exergy balances have been established around the  preheater-precalciner, the rotary kiln , the rotary cooler and the whole process. Energetic- and exergetic efficiency of the process attains  40%  and 25.7%  respectively . Sum of the exergy outputs attains about 49% of total exergy input and   irreversibility loss = 2354 kJ/kg clinker which represents about 51 % of total exergy input.  Energy and exergy of the by pass gases are the largest output loss items (  ~770 and 416 kJ/kg cli respectively) followed by those of the preheater exit gases (~ 622 and 152 kJ/kg cli respectively). For comparative purpose , the process was evaluated with considering no diversion of kiln gas  through by pass  . Energetic- and exergetic efficiency has been estimated in this case as  52%  and  34 %  respectively and the irreversibility attains  1840 kJ/kg clinker which represents about 52 % of total exergy input.